Interpersonal Communication Between Customers and Prospective Customers in Recommending EMJE Wedding Organizers (International Journal of Cultural and Social Science, 2023)
The purpose of this study is to find out how interpersonal communication between customers and prospective customers is in recommending EMJE Wedding Organizer and to find out the obstacles in interpersonal communication between customers and prospective customers in recommending EMJE Wedding Organizer. This research was conducted in Hamlet 1, Punden Rejo Village, Tanjung Morawa District. This study uses a qualitative approach that leads to a descriptive method. This study uses the theory of interpersonal communication initiated by De Vito. Collecting data in this study is by way of interviews, observation, and documentation. The data analysis technique used in this study is data reduction, data presentation and conclusion. Examination of the validity of the data in this study with seriousness in observation and triangulation. The results of this study found that the communication process went well between customers and prospective customers. By using De Vito's theory to describe the elements in interpersonal communication so that it is clear to know the communication process between customers, namely the existence of messages, feedback (feedback), feedforward, context and interpersonal competence. There are several things that customers do in the process of communicating with potential customers, namely: (a) forming perceptions of self-quality, (b) equating mindsets, and (c) helping to make choices. The communication process in recommending also has obstacles, namely, (a) language differences, (b) delays in understanding the contents of the message, and (c) time and distance. This study uses the theory of interpersonal communication by De Vito, which is in accordance with the results of the study namely, there are elements in the interpersonal communication process and there are obstacles in the process.